How to Understand Autism The Easy Way. - Durig, Alexander (Jessica Kingsley Publishers, 2004)
In this clear and accessible introduction to autism, Alexander Durig provides a host of ideas and examples that enable the reader to understand the phenomenon of autism, recognize different kinds of autistic perception and behaviour, and prepare for interaction with autistic people. To help 'normal' people understand and lose their fear of autism, Durig discusses the notions of 'slight' autism, being or becoming 'autism-friendly', and the mental well-being of autistic people. The author explains how autistic perception 'works' and how it yields autistic behaviours', to enable readers to see th.